Perhitungan Dinding Penahan Tanah Tipe Gravity Wall pada Tanah Pasir Berlanau di Bandara - Rizki Januardo; Fazetti Nazhifah; Viktor Suryan; Direstu Amalia (Politeknik Penerbangan Jayapura, 2026)
This study primarily aims to calculate and analyze a gravity-type retaining wall designed to support silty sand soil conditions at Zainuddin Abdul Madjid International Airport (BIZAM), Mandalika. The study's background is the need for stable supporting structures at airports, especially in areas where the ground level changes and aircraft operations put dynamic loads on them. The goal is to check how stable a gravity wall is against sliding, tipping over, and holding weight. The method uses field data, laboratory soil parameters, and relevant rules as a guide. It combines quantitative analysis with manual calculations. The analysis shows that a gravity wall that is three meters high and three meters wide at the base meets the safety factor requirements for sliding (FS = 2.0), overturning (FS = 2.4), and bearing capacity (FS = 3.9). Based on these results, the design is structurally sound for the type of soil specified. However, the design of the drainage system requires special attention because silty sand loses shear strength when it gets wet. The study's results show that gravity retaining walls can be put up successfully at airports with soft subgrade conditions, as long as safety and geotechnical data are carefully considered.